Errors Made by 8th Grade Students while Solving Mathematical Word Problems - Iilonga, Hesekiel Kaukolwa; Chirimbana, Moses (Journal of Research in Science and Mathematics Education, 2024)
Purpose: Mathematical word problems continue to challenge students due to their reliance on a range of interconnected mathematical concepts. This study investigates the specific types of errors students make when solving word problems, using Newman's Error Analysis as a framework. Methodology: Employing a descriptive-qualitative methodology, data were collected through tests and interviews with 47 eighth-grade students from a junior secondary school in the Ohangwena region of Namibia. Of these, nine students participated in interviews for a deeper understanding of their problem-solving processes. Findings: The analysis revealed that while no students experienced difficulties during the reading stage, significant challenges arose in later stages: comprehension errors occurred in 30.9% of cases, transformation and process skill errors were each observed in 62.2% of responses, and encoding errors, manifesting as inaccuracies in the final answer, were present in 62.8%. Significance: These findings highlight the critical need for educators to focus on enhancing students’ abilities to tackle word problems, particularly by incorporating assignments grounded in real-life scenarios to foster better comprehension and application of mathematical concepts.